PENGALIHAN UTANG DALAM EKONOMI ISLAM - fasiha, fasiha (Al-Amwal : Journal of Islamic Economic Law, 2016)
Debt in the Law of Islamic economics is called Al-Hiwalah. The legal basis Hiwalah application is the Qur'an, Hadith, Ijma and qiyas. Terms and harmonious Hiwalah is Muhil (Menghilawahkan), Second; Muhtal (in hilawahkan), third; Muhal 'alaih (people receiving Hiwalah, to four; Shighat Hiwalah, namely the consent of muhil. Hiwalah concept can be applied in the form of Islamic banking Factoring or factoring, post-dated check and Bill discounting